The Study of Serum Level of Interleukin-2, Interleukin-6, and Tumor Necrosis Factor-alpha in Stable and Progressive Vitiligo Patients from Sina Hospital in Tabriz, Iran - Mohammad Reza Ranjkesh; Mahya Rahimi Partovi; Mehrdad Pashazadeh (Indian Journal of Dermatology, 2021)
Background: Vitiligo is an acquired depigmenting disorder characterized by the loss of functional melanocytes from the epidermis. Although the etiology of vitiligo is unknown, over the last few years, substantial data from clinical research have greatly supported the "Autoimmune theory." Vitiligo has two major forms: progressive and stable. As cytokines are important mediators of immunity, the most important of them are IL-2, IL-6, and tumor necrosis factor-α (TNF-α). Objectives: We aimed to study the serum level of IL-2, IL-6, and TNF-α in stable and progressive vitiligo and compared them to find a useful lab test to determine the form of vitiligo for diagnose and treatment. Materials and Methods: Serum IL-2, IL-6, and TNF-α were done by the indirect enzyme-linked immunosorbent assay (ELISA) in 40 cases of stable and progressive vitiligo. Results: Twenty patients had progressive vitiligo and 20 patients were stable vitiligo. In every group, there were seven male patients. Twenty-one patients had a positive family history of vitiligo and four patients had other autoimmune diseases. The average age and familial history between two groups and two genders were not meaningful. The mean serum TNF-α level was significantly higher in progressive than stable vitiligo. No significant difference was observed in the serum levels of IL-2, IL-6 between stable and progressive vitiligo. The mean serum IL-6 and TNF-α had higher levels in male patients. Conclusion: Analysis of TNF-α levels in every age or gender can show us the type of vitiligo, stable or progressive and we can choose the best form of treatment for patients.